Effectiveness of Educational Objectives: Advancing the Quality of Education in Indonesia - Hoerul Ansori (Al-Hayat Al-Istiqomah Foundation, 2019)
In the contents of the Republic of Indonesia Constitution no. 20 of 2003 concerning National Education System is the realization of an education system as a strong and authoritative social institution to empower all Indonesians to develop into quality maneuvers that are capable and proactive in responding to the challenges of an ever-changing era. However, along with the rapid development of the times, with the emergence of various kinds of problems, especially in the field of education, which makes the goals of education contained in the law tend to be difficult to realize. So, to facilitate the development of educational goals with the aim of advancing the quality of education in Indonesia, there are three things that must be done, namely : 1) developing the quality of human resources, 2) building a Strong Educational Foundation and Clear Vision, 3) developing a noble moral based curriculum.Dalam undang-undang RI No. 20 tahun 2003 tentang Sisdiknas adalah terwujudnya sistem pendidikan sebagai pranata sosial yang kuat dan berwibawa untuk memberdayakan semua warga Indonesia berkembang menjadi manusia yang berkualitas sehingga mampu dan proaktif menjawab tantangan zaman yang selalu berubah. Akan tetapi, seiring dengan cepatnya perkembangan zaman, dengan munculnya berbagai macam permasalahan terutama dalam bidang pendidikan, yang membuat tujuan dari pendidikan yang tertuang dalam undang-undang tersebut cenderung sulit terwujudkan. Maka, untuk memudahkan pengembangan tujuan pendidikan dengan maksud memajukan kualitas pendidikan di Indonesia, ada tiga hal yang mesti dilakukan yaitu; 1) mengembangkan kualitas sumber daya manusia, 2) Membangun landasan pendidikan yang kuat dan visi yang jelas, 3) mengembangkan kurikulum berbasis akhlak mulia.